The Analysis of scientific papers related to intelligent forklifts - Espitia Cubillos, Anny Astrid; Jiménez-Moreno, Robinson; Rodríguez-Carmona, Esperanza (EASI: Engineering and Applied Sciences in Industry, 2025)
This document shows an analysis of documents related to intelligent forklifts, which seeks to identify the advances in the field and recognize the existing knowledge gap in the area to support the future design of a forklift that, based on artificial intelligence algorithms, can operate with certain autonomy and be called an intelligent forklift. The PRISMA 2020 guide is used for the search, selection, evaluation and summary of findings of the papers. We start with the search in the Scopus database, defining inclusion criteria to limit the study. The documents are characterized, then an analysis of their bibliographic networks is made using Wosviewer, after which their summaries are studied with Voyant, to succinctly present the main findings. It is concluded that it is important to promote collaborative work among authors, organizations and countries, to complement the advances in forklifts, their routing and movement planning using artificial intelligence tools, such as convolutional or transformer type networks.
Keywords: Artificial intelligence; Documental analysis; Documents,; Intelligent forklifts; Inventories